Light travel time effects in blazar flares - Finke, Justin D. (Frontiers in Astronomy and Space Sciences, 2024)
In this study, a model for light travel time effects for emission from a plasma blob in a blazar jet is presented. This calculation could be incorporated into more complex models with particle acceleration and radiation mechanisms, but as presented here, it is agnostic to these mechanisms. This model includes light travel time effects for an expanding or contracting blob. As examples, this model is applied to a flare observed by VERITAS and MAGIC from Mrk 421 in 2013 and a flare observed by the Fermi Large Area Telescope from 3C 454.3 in 2010.